2020
DOI: 10.1111/liv.14492
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Plin5 degradation by CMA causes lipid homeostasis imbalance in NAFLD

Abstract: Background & Aims: The pathological hallmark of nonalcoholic fatty liver disease (NAFLD) is an imbalance in hepatic lipid homeostasis, in which lipophagy has been found to play a vital role. However, the underlying molecular mechanisms remain unclear. We investigated the role of chaperone-mediated autophagy (CMA) in the pathogenesis of NAFLD. Methods: CMA activity was evaluated in liver tissues from NAFLD patients and highfat diet (HFD)-fed mice. Liver-specific LAMP2A-knockout mice and HepG2 cells lacking LAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…Further in vitro experiments revealed that LAMP3 overexpression resulted in higher expression of lipogenic genes. More evidence for a link between LAMP and NAFLD was demonstrated in livers of 24 NAFLD patients with varying degrees of steatosis (mild, moderate, severe) where a reduction of LAMP2A expression and other positive regulators of autophagy such as PLIN5 was found ( 92 ).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Further in vitro experiments revealed that LAMP3 overexpression resulted in higher expression of lipogenic genes. More evidence for a link between LAMP and NAFLD was demonstrated in livers of 24 NAFLD patients with varying degrees of steatosis (mild, moderate, severe) where a reduction of LAMP2A expression and other positive regulators of autophagy such as PLIN5 was found ( 92 ).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…As mentioned before, NAFLD is characterized by increased accumulation of LD in the liver as well as increased expression of PLIN5 [ 12 ]. This has been previously reported in patients with severe NAFLD as well as in mice fed with a high fat diet (HFD) inducing NAFLD [ 12 , 23 ].…”
Section: The Role Of Plin5 In Lipid Metabolism and Nafldmentioning
confidence: 99%
“…As mentioned before, NAFLD is characterized by increased accumulation of LD in the liver as well as increased expression of PLIN5 [ 12 ]. This has been previously reported in patients with severe NAFLD as well as in mice fed with a high fat diet (HFD) inducing NAFLD [ 12 , 23 ]. Interestingly, compared to PLIN5 protein levels, mRNA levels are only slightly increased, suggesting that elevated PLIN5 activity is regulated post-transcriptionally [ 12 ].…”
Section: The Role Of Plin5 In Lipid Metabolism and Nafldmentioning
confidence: 99%
See 2 more Smart Citations